Toys as Instructional Tools in Developing Problem-Solving Skills in Children - Clavio, Josefa Carina V.; Fajardo, Amelia C. (Philippine Journal of Education Studies (formerly the Education Quarterly); Vol. 66, No. 1 (December 2008), 2010)
This study determined possible uses of toys as instructional tools in the development of problem-solving skills among preschoolers. It aimed to identify the common toys found in preschool and how these toys can be used in lessons to develop students’ problem-solving skills. The first phase of the study was the selection of toys to be used in the lesson. The second was the designing of lessons integrating the development of problem-solving skills using toys identified in phase 1. The last is the evaluation of lessons developed in phase 2. Data were gathered using survey, observation, and document analysis. Lessons were developed using the Wallace and Maker Problem Solving Wheel. The study shows that the five commonly found toys in preschool classrooms have the potential to develop problem-solving skills in preschool children.